SOUTH AFRICA'S APPROACH TO CONFLICT MANAGEMENT IN BURUNDI AND THE DRC: PROMOTING HUMAN SECURITY? (The Strategic Review for Southern Africa, 2020)
This article is a critical reflection of South Africa's approach to conflictmanagement in Burundi and the Democratic Republic of Congo.These are countries in which South Africa has been extensively involved and which now serve as models for conflict management across the continent. The article highlights that though these interventions are often viewed as success stories South Africa's approach falls short of its intended objective of promoting human security. The article contends that South Africa's narrow focus on the state and war elites leaves key conflict generating issues unresolved and reinforces militarised authoritarian state structures. It has therefore paid lip service to creating more inclusive conflict management processes. South Africa has largely failed.to pioneer new ways of managing conflict that could lead to safer, resilient and prosperous societies.
Keywords: South Africa; conflict management; Burundi; Democratic Republic of Congo; state; war; militarised authoritarian state structures; human security